Giant fossil tortoise and freshwater chelid turtle remains from the middle Miocene, Quebrada Honda, Bolivia: evidence for lower paleoelevations for the southern Altiplano (2015)
We describe the first Miocene turtle remains from Bolivia, which were collected from the late middle Miocene (13.18–13.03 Ma) of Quebrada Honda, southern Bolivia. This material includes a large scapula-acromion and fragmentary shell elements conferred to the genus Chelonoidis (Testudinidae), and a left xiphiplastron from a pleurodire or side-necked turtle, conferred to Acanthochelys (Chelidae). The occurrence of a giant tortoise and a freshwater turtle suggests that the paleoelevation of the region when the fossils were deposited was lower than has been estimated by stable isotope proxies, with a maximum elevation probably less than 1000 m. At a greater elevation, cool temperatures would have been beyond the tolerable physiological limits for these turtles and other giant ectotherm reptiles.